Ink of Lanka - Samarawickrema, Tilak, 1943- (Colombo : Tilak Samarawickrema, 2009)
Photographic reproductions of drawings, etchings, and photographs of Tilak Samarawickrema, Sri Lankan architect and artist; includes appreciations on his life and work.
Keywords: Samarawickrema, Tilak, -- 1943-